Land Information System LIS as an Effective and Efficient Residential Layout Management Strategy (Global Journal of Human-Social Science, 2014)
Land Information System (LIS) can provide us a better and more efficient system for land management. This was used to develop an efficient system for the management of Tsaunin Kura residential layout in Chikun Local Government Area of Kaduna State, Nigeria. The study used topographical maps of Kaduna with sheet numbers 111 and 112 obtained from Kaduna state ministry of Land survey and town planning. The maps were scanned and geo-referenced to UTM-32 projection in a GIS environment and using the four procedures of reality, conceptual design, logical design and physical design. Using Arc GIS 9.2, the study was able to achieve the efficient and effective management of the land of the study area with the ability to identify the layout parcels, map it then generate data to provide a database that will enhance data collection, storage, manipulation, retrieval and dissemin-ation of information at precise and short time and eventually been able to query the database.
Keywords: LIS; database; layout; query